Development of metal matrix composites and related forming techniques by direct recycling of light metals: a review - Al-Alimi, Sami; Lajis, Mohd Amri; Shamsudin, Shazarel; Chan, B.L.; Mohammed, Yahya; Ismail, Al Emran; Sultan, N. M. (UTHM Publishing, 2020)
In this contribution, researchers have provided a summary of the agricultural and industrial waste recoveries to be deployed as the composite reinforced materials. It covers the work of previous researchers related to this area and addressed the key challenge to overcome for further development and advancement. The major contributions of this work were a comprehensive review on a wide variety of Sever Plastic Deformation (SPD) techniques implementation in development of the waste materials based reinforced metal matrix composite. The waste materials can be derived from either industrial or natural sources. Also, it discusses the range of Metal Matrix Composites (MMCs) applications in engineering and related manufacturing techniques with further emphasized on the process parameters which directly determine the material properties. Some useful suggestions were proposed to the industrialists, academicians and scientists to further improve the performance aspect of MMCs for commercialization reason. Furthermore, industrial and natural waste enhancement materials have been strongly proposed because of their higher reinforced content particulates such as alumina (Al2O3) and silica (SiO2). Also, the mechanical and physical properties are directly influenced by the size, shape and weight-volume fraction of the composites as same as the potential reactions between matrixes/reinforced materials interface.